Outcomes of Cooled Radiofrequency Ablation of Lumbar Nerves as Treatment for Chronic Low Back Pain - Alaa Abd-Elsayed; Trevor N. Johnson; Kylie K. Ruprecht; Tristan R. Argall; Lukas J. Henjum; Kenneth J. Fiala (Pain and Therapy)
Abstract Introduction Worldwide, 23% of adults suffer from chronic lower back pain, which is defined as pain persisting for more than 3–6 months [Merskey in Can J Psychiatry 34:329–336, 1989]. The lifetime prevalence of back pain is as high as 84% in adults [Casiano VE, Sarwan G, Dydyk AM, et al. Back Pain. [Updated 2023 Dec 11]. In: Stat Pearls [Internet]. Treasure Island (FL): Stat Pearls Publishing; 2024 Jan-. Available from: https://www.ncbi.nlm.nih.gov/books/NBK538173/ ]. Conservative treatment options for chronic low back pain include as needed or scheduled analgesics, physical therapy, anticonvulsants, exercise, weight loss, muscle relaxants, and much more. With chronic pain that is refractory to the aforementioned treatments, more invasive procedures may be indicated. Cooled radiofrequency ablation (CRFA), a minimally invasive therapy, utilizes internally cooled radiofrequency probes to deliver targeted thermal energy that causes neurolysis, disrupting the transmission of pain stimuli along nociceptive pathways, thus resulting in pain relief [Walker in J Spinal Disord 13:205–217, 2000 June]. This study investigates whether patients receiving CRFA for relief of chronic low back pain caused by lumbar facet arthropathy experience a reduction in pain scores, the length of this reduction in pain scores, and the magnitude of this reduction in pain. Methods This study was a retrospective analysis of data extracted from UW-Health Electronic Medical Health records (EMR), encompassing lumbar CRFA procedures performed from 2015 through April of 2024. Patient data was obtained, including diagnosis, preoperative pain score, postoperative pain score, duration of relief, patient age, sex, and BMI. A two-tailed paired t test was used to statistically analyze the preoperative and postoperative pain scores, in which a p value ≤ 0.05 was considered significant. Results A total of 1450 lumbar CRFA procedures were reviewed, and 206 were excluded due to absent pre- or post-op pain scores. An additional eight procedures were excluded due to weekly lidocaine infusions in between their procedure and reporting of their post-op score. 1026 CRFA patients were included in the analysis, comprising 584 females and 442 males with an average age of 59.81 ± 13.40 and a BMI of 31.67 ± 7.13. The average pre-procedure visual analog scale (VAS) pain score was 6.44 (6.44 ± 1.67, n = 1236), and the average post-procedure VAS pain score was 3.21 (3.21 ± 2.45, n = 1236) this achieved statistical significance (p < 0.0001). Improvement of pain symptoms was reported in 85.92% (n = 1062), 14.08% (n = 174) reported complete pain remission, 7.61% (n = 94) reported no change, and 6.47% (n = 80) reported worsening symptoms. For effective procedures (those with any amount of pain relief, n = 1062) with an available postoperative pain score, the mean percentage improvement was 60.56 ± 27.21%. The average duration of improvement was 267.43 ± 393.18 days. Conclusions This study supports the potential efficacy of CRFA as a minimally invasive treatment for chronic back pain secondary to lumbar facet arthropathy refractory to conventional treatment measures, demonstrating significant relief for a substantial length of time. Due to chronic pain’s detrimental effect on one’s quality of life, finding effective treatment options is essential, especially for those refractory to conventional treatments.